Certain remarks on the experience of teaching the international humanitarian law - Artur H. Ibragimov, Sadagat Bashirova, Uzeyir Y. Mammadov, (Opción, 2019)
This article is devoted to the multidimensional problems of teaching the international humanitarian law in the Russian higher school through pedagogical and survey research methodologies. As a result, teaching such a unique discipline requires a solid share of wisdom and a special approach that depends largely on a number of different factors that seem to be taken into account in the teaching process. As a conclusion, the high level of education not only in the IHL, but also in other branches of law is considered as the basis of a free democratic society